1982
DOI: 10.1093/nar/10.23.7477
|View full text |Cite
|
Sign up to set email alerts
|

The sequences homologous to major interspersed repeats B1 and B2 of mouse genome are present in mRNA and small cytoplasmic poty(A)+RNA

Abstract: Heavy nuclear RNA contains high amounts of transcripts from repetitive sequences B1 and B2. Cytoplasmic poly(A)+RNA and, particularly, polysomal poly(A)+RNA (mRNA) also include these sequences but in smaller amounts. The abundant 2 kb mRNA of mouse liver are found to have a B2 sequence. These sequences are also found in a new class of low-molecular-weight heterogeneous (200-400 nucleotide long) poly(A)+RNAs. These RNAs are located mostly in cytoplasm rather than in polysomes. The amount of small B2+ RNAs is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
32
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…For Bi, we observed the 7S and 4.5S RNA transcripts described by others (30). Apart from the previously described 20S RNA transcript (31), no other discrete RNA transcripts hybridized to the B2 probe. The R and MIF-1 probes only hybridized to a very faint smear of transcripts.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…For Bi, we observed the 7S and 4.5S RNA transcripts described by others (30). Apart from the previously described 20S RNA transcript (31), no other discrete RNA transcripts hybridized to the B2 probe. The R and MIF-1 probes only hybridized to a very faint smear of transcripts.…”
supporting
confidence: 61%
“…We do not know whether these small B2 transcripts are synthesized by PollI or PolIII. The B2 sequence includes all of the necessary regulatory sites for initiation and termination by PollIl (31). Our transcription elongation analysis in nuclei has shown that both Bi and B2 sequences are included in Po/IlI as well as Polll transcripts in the liver ( Table 2).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Both Bi and B2 repeats have the same approximate size, 130 and 160 base pairs (bp) respectively, are characterized by an A-rich tract at their 3' ends, are often flanked by short direct repeats at their site of insertion in the genome, and contain putative RNA polymerase III promoter regions (18,24). In vitro and in vivo transcription of a few individual Alu-type elements by RNA pol III has been reported (6,10,17,37).…”
mentioning
confidence: 99%